Analysis Of Village Direct Cash Assistance Policy Implementation In East Bolaang District Bolaang Mongondow Regency - Dilapanga, Abdul Rahman; Pangalila, Theodorus; Supit, Brian Fransisco (Technium Social Sciences Journal, 2023)
Since the end of 2019, all countries have been shocked by the spread of Covid-19. Indonesia is one of the countries affected by the ongoing global disease pandemic (COVID-19). The pandemic has spread to 34 provinces. Covid-19 has had an enormous impact on the economic sector, and the government has assisted, one of which is the Village Fund Direct Cash Assistance (BLT). The Direct Cash Assistance (BLT) policy is an alternative policy dealing with the impact of the spread of Covid-19. In various media, there is a lot of news about the implementation of the BLT program, which often deviates from the applicable provisions. Therefore, analyzing the implementation of the BLT program is very important. Village Fund Direct Cash Assistance (BLTDD) is the government’s response in minimizing the impact of Covid-19 on the people in the village. In the early stages of its implementation, problems were found in the form of community protests against village officials who were deemed unable to implement the Village Fund BLT policy properly. Even in some villages, it led to the destruction of the village office. On this basis, this research aims to analyze the problems that arise in implementing the Village Fund BLT policy to identify issues and challenges so that they become materials for improvement. This research was conducted with a qualitative approach. Since the end of 2019, all countries have been shocked by the spread of Covid-19. Indonesia is one of the countries affected by the ongoing global disease pandemic (COVID-19). The pandemic has spread to 34 provinces. Covid-19 has significantly impacted the economic sector, and the government has assisted, one of which is the Village Fund Direct Cash Assistance (BLT). The Direct Cash Assistance (BLT) policy is an alternative policy dealing with the impact of the spread of Covid-19. In various media, there is a lot of news about the implementation of the BLT program which often deviates from the applicable provisions. Therefore, analyzing the implementation of the BLT program is very important. Village Fund Direct Cash Assistance (BLTDD) is the government’s response in minimizing the impact of Covid-19 on the people in the village. In the early stages of its implementation, problems were found in the form of community protests against village officials who were deemed unable to implement the Village Fund BLT policy properly. Even in some villages, it led to the destruction of the village office. On this basis, this research aims to analyze the problems that arise in implementing the Village Fund BLT policy to identify issues and challenges so that they become materials for improvement. This research was conducted with a qualitative approach.